Magnetic resonance imaging for in vivo assessment of three-dimensional patellar tracking. - Fellows, R; Hill, N; Gill, R; MacIntyre, N; Harrison, M; Ellis, R; Wilson, DR (2005)
We have developed a non-invasive measurement technique which can ultimately be used to quantify three-dimensional patellar kinematics of human subjects for a range of static positions of loaded flexion and assessed its accuracy. Knee models obtained by segmenting and reconstructing one high-resolution scan of the knee were registered to bone outlines obtained by segmenting fast, low-resolution scans of the knee in static loaded flexion. We compared patellar tracking measurements made using the new method to measurements made using Roentgen stereophotogrammetric analysis in three cadaver knee specimens loaded through a range of flexion in a test rig. The error in patellar spin and tilt measurements was less than 1.02 degrees and the error in lateral patellar shift was 0.88 mm. Sagittal plane scans provided more accurate final measurements of patellar spin and tilt, whereas axial plane scans provided more accurate measurements of lateral translation and patellar flexion. Halving the number of slices did not increase measurement error significantly, which suggests that scan times can be reduced without reducing accuracy significantly. The method is particularly useful for multiple measurements on the same subject because the high-resolution bone-models need only be created once; thus, the potential variability in coordinate axes assignment and model segmentation during subsequent measurements is removed.